PENGARUH RELATIONSHIP MARKETING TERHADAP LOYALITAS NASABAH (Studi Nasabah Tabungan Sinar Belia PT.Bank Riau Kepri Cabang Pekanbaru) - ", Riesmanto; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the effect of relationship marketing on customer loyalty at PT. Bank Riau Kepri. Relationship marketing as an independent variable (X) has been formulated that is seen from Communication, Trust, Commitment and Problem solving. Customer Loyalty as the dependent variable (Y). This research was conducted on all fixed customers at PT. Riau Bank Riau Islands as many as 100 people.Data were obtained from the questionnaire and then processed for later tested using statistical analysis such as simple linear regression analysis, t test, and correlation and determination analysis using SPSS assistance.The results showed that the results of hypothesis testing t arithmetic greater than t table that is 10,854> 2,838. This shows that relationship marketing affects customer loyalty.Keywords: Relationship Marketing, Customer Loyalty